Impact of an online WHO mental health guideline-based training on stigma and clinical confidence among non-psychiatrist physicians in Mexico: a pre-experimental pilot study - Vargas-Huicochea, Ingrid; Rodríguez-Machain, Ana Carolina; Tafoya, Silvia A. (Frontiers in Public Health, 2025)
IntroductionMental health is a critical component of overall well-being, and the stigma associated with mental illness often prevents healthcare professionals from providing adequate care. This is a pilot study designed to evaluate the feasibility of an educational intervention and its preliminary effects on stigma associated with mental illness and the subjective assessment of capacity, clinical experience, and perceived limitations in managing mental disorders among non-psychiatrist physicians.MethodsA pre-experimental design was used, including measurements before (Pre), immediately after (Post), and Follow-up at 12 months after the intervention (F-12 m). The sample consisted of non-specialist doctors who were invited to a training program of mhGAP and all scheduled assessments. Inclusion criteria were: being an active non-psychiatrist doctor, providing informed consent, and availability to participate in all three phases of the study. The online training program was based on the WHO mhGAP guidelines and it was administered over a period of 5 weeks in three groups in February, March and August 2023. The instruments used were the Mental Illness Clinician Attitudes (MICA) and the Attitudes, Confidence, and Behavior Questionnaire (ARCBQ), which measures capacity, experience, and limitations perceived in managing patients with mental illness.ResultsOf the 69 doctors enrolled, 39 (57%) were drop-outs and 30 (43%) completed the training and all evaluations. The results show a significant decrease in stigma and a notable increase in perceived capacity and clinical experience over time. However, perceived limitations did not change significantly.ConclusionThe intervention has important implications for physician training and suggests the need for a more inclusive and sustainable approach to continuing mental health education. These findings pave the way for future research on the longitudinal impact of such changes and their applicability across diverse cultural and demographic contexts.